2018
DOI: 10.1002/acr.23556
|View full text |Cite
|
Sign up to set email alerts
|

Determining One‐Year Trajectories of Low‐Back–Related Leg Pain in Primary Care Patients: Growth Mixture Modeling of a Prospective Cohort Study

Abstract: Four trajectories of leg pain were identified. Clusters 1, 2, and 3 were generally comparable to back pain trajectories, while cluster 4, with major improvement in pain, is infrequently identified. Awareness of such distinct patient groups improves understanding of the course of leg pain and may provide a basis of classification for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Many studies have identified clusters of pain trajectories among individuals living with chronic pain. Some have focused on participants with 1 chronic pain condition, such as osteoarthritis [ 15 , 36 - 39 , 52 - 58 ], low back pain [ 13 , 14 , 27 , 59 - 65 ], other back pain [ 25 , 32 , 49 , 66 ], neck or shoulder pain [ 33 , 61 , 67 , 68 ], leg pain [ 29 ], knee pain [ 69 ], or foot pain [ 70 ], whereas others have identified clusters among a broader population, such as those with musculoskeletal pain [ 26 , 31 , 47 , 71 , 72 ] or general pain [ 48 , 73 - 75 ]. Clusters in these studies were described by the severity of pain (eg, no pain , very low pain , mild pain , moderate pain , high pain , and severe pain ), the level of change in pain severity (eg, persistent , ongoing , episodic , worsening , recovering , and fluctuating ), or a combination of these features.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified clusters of pain trajectories among individuals living with chronic pain. Some have focused on participants with 1 chronic pain condition, such as osteoarthritis [ 15 , 36 - 39 , 52 - 58 ], low back pain [ 13 , 14 , 27 , 59 - 65 ], other back pain [ 25 , 32 , 49 , 66 ], neck or shoulder pain [ 33 , 61 , 67 , 68 ], leg pain [ 29 ], knee pain [ 69 ], or foot pain [ 70 ], whereas others have identified clusters among a broader population, such as those with musculoskeletal pain [ 26 , 31 , 47 , 71 , 72 ] or general pain [ 48 , 73 - 75 ]. Clusters in these studies were described by the severity of pain (eg, no pain , very low pain , mild pain , moderate pain , high pain , and severe pain ), the level of change in pain severity (eg, persistent , ongoing , episodic , worsening , recovering , and fluctuating ), or a combination of these features.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining or treating this functionality is important for spine physicians to preserve or improve life quality and eventually get patients back to work. In recent years new research has identified clinically relevant clusters of patients presenting with low back pain (35)(36)(37) and backpain related leg pain (25,26,28,(38)(39)(40). Although several classification systems have been published, very few have focused and include patient reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain is a challenge to manage, and many patients with persistent LBP might have neuropathic pain that does not respond to existing treatments (Baron et al, ). Previous longitudinal modelling on a cohort of patients with low back‐related leg pain identified a “persistent severe” and “improving severe” group (Ogollah, Konstantinou, Stynes, S., Dunn, ). The characteristics that distinguished the persistent severe group were the patients who were more likely to report leg pain of potential neuropathic nature (measured using the self‐report Leeds Assessment Neuropathic Symptoms and Signs (S‐LANSS) questionnaire) than those in the “improving severe” group.…”
Section: Discussionmentioning
confidence: 99%